Characterization of polar surface groups on siliceous materials by inverse gas chromatography and the enthalpy–entropy compensation effect - Meyer, Ralf; Mueller, Kai; Naumov, Sergej; Bauer, Frank; Enke, Dirk (Frontiers in Chemistry, 2023)
Surface modified porous silica is a well-established composite material. To improve its embedding and application behavior, adsorption studies of various probe molecules have been performed using the technique of Inverse gas chromatography (IGC). For this purpose, IGC experiments were carried out in infinite dilution (ID) mode on macro-porous micro glass spheres before and after surface modification with (3-Mercaptopropyl)-trimethoxysilane (MPTMS). To provide information about the polar interactions between probe molecules and the silica surface, in particular, eleven polar molecules have been injected. In summary the determination of the free surface energy for pristine silica (γ_S^total = 229 mJ/m²) and for MPTMS modified silica (γ_S^total = 135 mJ/m²) indicates a reduced wettability after surface modification. This is due to the reduction of the polar component of the free surface energy (γ_S^SP ) from 191 mJ/m² to 105 mJ/m². Simultaneously with the reduction of surface silanol groups caused by surface modification of silica and therefore the decrease in polar interactions, a substantial loss of Lewis-acidity was observed by various IGC approaches. Experiments with all silica materials have been conducted at temperatures in the range from 90 to 120°C to determine the thermodynamic parameters, such as adsorption enthalpy (〖ΔH〗_ads) and adsorption entropy (〖ΔS〗_ads) using the Arrhenius regression procedure evaluating the IGC data. With the help of the enthalpy-entropy compensation two types of adsorption complexes are assumed between polar probe molecules and the silica surface because of different isokinetic temperatures. Identical adsorption complexes with an isokinetic temperature of 370 °C have been assigned to alkanes and also weakly interacting polar probes such as benzene, toluene, dichloromethane, and chloroform. Polar probe molecules with typical functional groups such as OH, CO, CN, etc., having the ability to form hydrogen bonds to the silica surface, exhibit a lower isokinetic temperature of 60 °C. Quantum chemical calculations of the probe molecules on a non-hydroxylated and hydroxylated silica cluster supported the formation of hydrogen bonds in the case of strong polar adsorption complex with bonding distance of 1.7 nm to 1.9 nm to the silica surface.